Infrastructure Management and Early Childhood Education Teachers’ Deep Learning Readiness in Indonesia - Asep Mumung; Fitriyani Kosasih (International Journal of Social Learning (IJSL), 2026)
Deep learning is an essential approach in Early Childhood Education (ECE). However, its implementation in practice has not been fully optimal, as many educators see it as just a curriculum rather than a pedagogical approach. This study explores how prepared teachers are to apply the three core pillars of deep learning: mindful, meaningful, and joyful learning. Using a descriptive qualitative method, the research employs triangulation through observation, interviews, and document analysis at RA Azzahra Majalengka. The results show that these pillars are in use, but their application is only partial and not yet at an excellent standard. Teachers create opportunities for exploration, but reflection is limited; activities meant to be meaningful are not well integrated across subjects; and enjoyable learning tends to be overly structured. These findings highlight the need for equal, comprehensive deep learning training for all ECE teachers to enhance their ability to create meaningful, holistic learning experiences.